Biases and Reluctances Causing Cancer Patients in Dilemma for COVID-19 Vaccination (Bangladesh Journal of Medical Science, 2024)
Background  We have planned this study to determine opinions of this patient group, who are affected negatively both in physical aspect during the treatment process of cancer and who are fragile and sensitive for psycho-social aspects, their opposition level and misimpressions related to vaccine and for eliminating these reluctances if possible.Methods  Between February 2021 and 15 April 2021, all cancer patients applying to our oncology clinic have been first asked to fill in the questionnaire, which includes three articles where suggestions expressing their attitude towards vaccination were asked and subsequently nine articles expressing suggestions about vaccine oppositionResults  According to responses to a decision for vaccination, we have learned that 446 (79,6%) patients thought to have the Covid-19 vaccine, 62 (11.1%) were hesitant, and 52 (9.3%) did not think to have a vaccine.Conclusions  The most critical data obtained from this study is that there were severe biases related to adverse effects due to vaccines, although patients have a positive attitude about vaccination. The most important task of health authorities should be to eliminate reluctance without waiting for patients to take a more negative attitude on this subject.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 345-354